2011
DOI: 10.4028/www.scientific.net/msf.688.383
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pulsed Magnetic Field Treatment on the Magnetic Properties of the Fe-Nd-Al-B Alloys Prepared by Suction Casting

Abstract: The magnetic properties of the (Fe0.53Nd0.37Al0.10)96B4bulk amorphous alloys annealed in the temperature range of 293-623K for 30 min with and without an external pulsed magnetic field of 5T were studied. The results reveal that the remanence and coercivity of the samples are obviously improved with a pulsed magnetic field when annealed below the Curie temperature of the alloy. The increment of remanence reaches 25.9% for the sample annealed at 523K with a pulsed magnetic field, because of the enhancement of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Magnetic field annealing and processing have been widely used to improve magnetic performance of soft and hard magnets as well as properties of non-magnetic systems. [1][2][3][4][5][6][7][8][9] The grain size refinement, texture enhancement and magnetic property improvement were observed in the bulk NdFeB magnets prepared by injection casting in a magnetic field. 10 The grain size refinement under a magnetic field during the solidification was observed in the Sn-Pb system.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Magnetic field annealing and processing have been widely used to improve magnetic performance of soft and hard magnets as well as properties of non-magnetic systems. [1][2][3][4][5][6][7][8][9] The grain size refinement, texture enhancement and magnetic property improvement were observed in the bulk NdFeB magnets prepared by injection casting in a magnetic field. 10 The grain size refinement under a magnetic field during the solidification was observed in the Sn-Pb system.…”
Section: Introductionmentioning
confidence: 94%
“…11 It was also found that the field changes the phase equilibrium of the system, e.g., shifts the eutectic point in the Mn-Sb system to the Mn-rich concentration 12 and even shifts the temperature-time-transformation (TTT) diagram of the isothermal martensitic transformation in the Fe 24.9 Ni 3.9 Mn alloy. 13 The field strength used in the experiments was in the Tesla range [1][2][3][4][5][7][8][9][10][11][12][13] except the small value of 90 Oe used in the work for the amorphous ribbons. 6 In this work the effect of a magnetic field acting directly on the rapid quench solidification of the ferromagnetic system NdFeB/Fe was investigated.…”
Section: Introductionmentioning
confidence: 99%